Comparative proteomic analysis of self-compatible and self-incompatible genotypes of fennel (Foeniculum vulgare Mill.) - Zahra Mirzahosseini; Leila Shabani; Mohammad R. Sabzalian; Samira Shojaiefar; Selvadurai Dayanandan (BMC Plant Biology)
Abstract In this study, a comparative proteomic analysis was conducted on four agriculturally important genotypes of fennel (Foeniculum vulgare Mill.) named Yazd, Tabriz, Varamin, and Karaj to identify effective proteins and mechanisms involved in self-incompatibility. Self-pollinated and open-pollinated seeds from each genotype were planted in separate lines. Then, three umbels of selected plants were enveloped for re-self-pollination, while the other umbels were pollinated by bees. All experiments, including quantification of total protein concentration and mass spectrometry analysis (LC–MS/MS), were carried out on the flower styles from self-compatible and self-incompatible plants of the studied populations. Additionally, the essential oil content of selected plants was measured to assess its correlation with pollination type (or self-compatibility) and genotypes. Results showed that, regardless of the plant genotype, self-incompatibility doubled the total protein content. The highest protein concentration was measured in the Karaj self-incompatible genotype, while the lowest was found in the Yazd self-compatible genotype. Proteomic analysis revealed genotype-specific upregulation of proteins involved in essential oil biosynthesis in fennel, particularly in response to self-incompatibility (SI). While SI induced significant proteomic changes linked to metabolic pathways, the impact on essential oil content varied across genotypes, highlighting the complex interplay of genetic, enzymatic, and environmental factors in essential oil production. The results also indicated that the response of the fennel plant to self-compatibility is strongly correlated to the plant's genotype. According to the results, although plant genotype specifically affects the plant's protein expression profile under self-incompatibility conditions, proteins involved in the production of energy and metabolites necessary for fertilization and compatible crosses, as well as proteins involved in pollen tube formation and growth, are considered key proteins involved in self-compatibility in all studied genotypes. The results proposed a sporophytic mechanism for self-incompatibility in fennel.